Extension strategies to enhance wheat production in India - Singh, Randhir; Kumar, Anuj; Cummins, Jay; Singh, Satyavir; Singh, S S (Indian Farming, 2015)
With the existing wheat production technologies, an additional wheat production can be attained by adopting the technologies. Apart from addressing the issue of land consolidation particularly in the state of Bihar, poor seed replacement, late sowing, poor quality seed, leaf blight, water stress, imbalanced fertilization, varietal diversification and Phalaris minor are the important issues. Concerted efforts need to be made across the country, particularly in the states of Bihar, UP, Rajasthan and MP. The farmers should be made aware that full adoption of the recommended technology is the key to enhance wheat production and not the partial adoption. The extension workers should use the latest information communication technologies along with the traditional extension methods to put across the message to the farmers.